Small Business Manager’s Profile and Financing Constraints: The Moderate Role of Sociocultural Factors - Eriola, Jesse Akitola; Hounkou, Emmanuel Cossi (Journal of Leadership, Accountability and Ethics, 2022)
This study first analyses the effect of SBs managers’ characteristics on the difficulties in obtaining financing. Secondly, we highlight the moderate role of sociocultural factors in this relationship. Based on the hypothesis that sociocultural factors such as solidarity, rotative tontine, and supplier proximity moderate the relationship between the manager’s profile and perceived difficulties in obtaining financing, logistic regression is realized using questionnaire survey data from a sample of Beninese SBs’ managers. Overall, the findings show that in the majority, of the SBs managers are male, older, and have a minimum education. Almost half of the respondents have benefited from the support of their family or friends (solidarity) and practice the rotative tontine. Perceived difficulties in obtaining financing are affected by age, gender, manager’s link, and experience. We also found that solidarity, rotative tontine, and supplier proximity impact significantly perceived problems in obtaining financing and these sociocultural factors moderate the relationship between managers and perceived difficulties. Overall, given the findings, we suggest that government may target and organize the informal finance.